EFEKTIFITAS KONSUMSI JANTUNG PISANG BATU (MUSA BALBISIANA COLLA) TERHADAP PRODUKSI ASI PADA IBU POST PARTUM DI WILAYAH KERJA PUSKESMAS SELATBARU - Maysari, Nani; Oktora Sri, Ary; Susanti, Komaria; Sari Tanberika, Fajar (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Breast milk (ASI) contains nutrients according to the baby's needs for growth, immunity, preventing various diseases and for the baby's intelligence. Banana flower is one of the plants containing lactagogum which can stimulate the hormones oxytocin and prolactin. The purpose of this study was to determine the Effect of Consumption of Batu Banana Flower (Musa Balbiana Colla) on Breast Milk Production in Postpartum Mothers in the Selatbaru Health Center Work Area. The research design was pre-experimental with One Group Pretest-Posttest. The sampling technique used Accidental sampling with a population of postpartum mothers with a sample size of 16 respondents. Breast milk production before consuming boiled banana flower from 16 respondents was (68.0%) sufficient breast milk production, (25.0%) insufficient breast milk production and (6.3%) high breast milk production. Breast milk production after consuming boiled banana flower was (93.8%) high breast milk production and (6.3%) low breast milk production. There is an effect of Banana Heart Consumption (Musa Balbisiana Colla) on Breast Milk Production in Postpartum Mothers with a p-value = 0.000. It is recommended that by giving banana heart consumption and explaining the benefits of banana heart for breast milk production, postpartum mothers can consume banana heart while breastfeeding as an effort to increase breast milk production to support exclusive breastfeeding and it is expected to be used as one of the materials for conducting counseling on foods that can facilitate breast milk to support exclusive breastfeeding.Keywords: Breast Milk Production, Banana Heart Stone, Post Partum.